2013
DOI: 10.1177/1748048513482545
|View full text |Cite
|
Sign up to set email alerts
|

Al-Jazeera and Al-Arabiya framing of the Israel–Palestine conflict during war and calm periods

Abstract: This framing study compares Al-Jazeera and Al-Arabiya coverage of the Israel–Palestine conflict during the 2008/2009 Gaza conflict and one year later, during a period of calm. Findings suggest that both networks used framing mechanisms to highlight Palestinian perspectives over Israeli ones and frame Palestinians as victims of Israeli aggression. The networks regularly described Palestinian casualties and showed images of Palestinian grief, provided more voice to Palestinian sources, and personalized Palestini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…The Al-Arabiya channel is currently based in Dubai and funded by Saudi Arabia (Lynch, 2006 These two media outlets provide typical examples of how translation in news is being conducted in real-life surroundings. Aljazeera and Al-Arabiya are considered leading regional news providers in the region (Elmasry et al, 2013). An article published on Aljazeera's website shows that it is the most-watched news channel in the Middle East and North Africa, according to the research agencies IPSOS and SIGMA (Aljazeera, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…The Al-Arabiya channel is currently based in Dubai and funded by Saudi Arabia (Lynch, 2006 These two media outlets provide typical examples of how translation in news is being conducted in real-life surroundings. Aljazeera and Al-Arabiya are considered leading regional news providers in the region (Elmasry et al, 2013). An article published on Aljazeera's website shows that it is the most-watched news channel in the Middle East and North Africa, according to the research agencies IPSOS and SIGMA (Aljazeera, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, framing research is not without its critics, especially when it comes to variance among studies (Elmasry, El Shamy, Manning, Mills, & Auter, 2013). This current study aims to contribute to a specific area of framing research, naming framing of conflict and terrorism, as elaborated in the following section.…”
Section: Framing Theorymentioning
confidence: 99%
“…Al Arabiya was established in 2003 in Dubai by the Middle East Broadcasting group (MBC), which is owned by a Saudi businessman with close ties to the Saudi monarchy. The network enjoys high viewership in the Arab region (Al-Rawi, 2016; Elmasry et al, 2013; El-Nawawy and Strong, 2012b; Nisbet and Myers, 2011), often ranking second in viewership to Al Jazeera (El-Nawawy and Strong, 2012a).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the case of Al Jazeera, research suggests that the network’s attempt to present and defend otherwise marginalized perspectives may sometimes influence it to take sides in political conflicts. For example, studies by Barkho (2011) and Elmasry et al (2013) have found that Al Jazeera news framing strongly favours Palestinian perspectives over Israeli perspectives in the Israel–Palestine conflict, while a separate study by Jasperson and El-Kikhia (2003) found that Al Jazeera’s framing of United States foreign policy in the Middle East was overtly critical and negative. In addition, a study by El-Nawawy and Elmasry (2015) suggested that Al Jazeera’s coverage of the 2011 Egyptian uprising framed the event in a way that enthusiastically embraced the anti-government protesters.…”
Section: Framingmentioning
confidence: 99%